Utilization of Zakat for Persons with Disabilities in a Muslim-Minority Region: Study in Tana Toraja - Rahmawati Muin; Ayu Ruqayyah Yunus; Andi Muh. Taqiyuddin BN; Suprijati Sarib; Ega Rusanti; Muh. Bambang Taufik (Jurnal Ilmiah Al-Syir'ah, 2026)
This study examines the institutional challenges of zakat distribution for persons with disabilities in Tana Toraja, a Muslim-minority region in Indonesia. Using a qualitative fieldwork design, data were collected through semi-structured interviews with BAZNAS officials, local government representatives, disability organization actors, and zakat beneficiaries. The findings show that zakat assistance for persons with disabilities remains at an early and fragmented stage. Productive assistance has been provided in the form of livestock, while consumptive assistance has addressed basic needs; however, the program has not yet been institutionalized in BAZNAS Tana Toraja’s short-, medium-, or long-term planning. The absence of an integrated disability database, weak coordination with local agencies, limited fiscal support, and the lack of local zakat regulation constrain program sustainability. Using Talcott Parsons’ AGIL framework, this study argues that adaptation and integration have begun but remain partial, while goal attainment and latency have not been fully achieved. The article contributes to Islamic economic law by highlighting the need for inclusive zakat governance in Muslim-minority regions.